Enteric Polymer–Based Amorphous Solid Dispersions Enhance Oral Absorption of the Weakly Basic Drug Nintedanib via Stabilization of Supersaturation - Yuling Qin; Chuyao Xiao; Xiaoyue Li; Jiangeng Huang; Luqin Si; Minghui Sun (Pharmaceutics, 2022)
The pH–induced crystallization of weakly basic drugs in the small intestine limits oral bioavailability. In this study, we investigated the solubilization and inhibitory effects on nintedanib in the presence of enteric polymers (HPMCAS LG, HPMCAS MG, Eudragit L100 55, and Eudragit L100). These polymers provided maintenance of supersaturation by increasing the solubility of nintedanib in PBS 6.8 in a concentration-dependent manner, and the improved ranking was as follows: Eudragit L100 > Eudragit L100 55 > HPMCAS MG > HPMCAS LG. After being formulated into amorphous solid dispersions (ASDs) by a solvent evaporation method, the drug exhibited an amorphous state. The pH shift dissolution results of polymer-ASDs demonstrated that four polymers could effectively maintain the drug supersaturation even at the lowest ratio of nintedanib and polymer (1:1, w/w). Eudragit L100–ASD could provide both acid resistance and the favorable mitigation of crystallization in GIF. In comparison to the coarse drug, the relative bioavailability of Eudragit L100–ASD was 245% after oral administration in rats, and Tmax was markedly delayed from 2.8 ± 0.4 h to 5.3 ± 2.7 h. Our findings indicate that enteric ASDs are an effective strategy to increase the intestinal absorption of nintedanib by improving physiologically generated supersaturation and subsequent crystallization.